The Influence of Self-Efficacy, Sharia Financial Literacy and Social Influence on Entrepreneurial Decisions (Case Study of PUSKIIBI UMSU) - Anisa Madani Nasution; Zuhrinal M Nawawi; Nursantri Yanti (Indonesian Journal of Islamic Economics and Finance, 2026)
Entrepreneurial decisions are influenced by various internal and external factors, such as self-confidence, understanding of financial management, and social support. This study aims to analyze the influence of self-efficacy, Islamic financial literacy, and social influence on the entrepreneurial decisions of students at the Center for Entrepreneurship, Innovation, and Business Incubator (PUSKIIBI) at the University of Muhammadiyah North Sumatra. This study used a quantitative approach with an explanatory research method. The study population was 50 active student members of PUSKIIBI UMSU using a total sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (SEM-PLS). The results showed that Islamic financial literacy and self-efficacy had a positive and significant effect on entrepreneurial decisions, with Islamic financial literacy as the most dominant variable. Conversely, social influence did not have a significant effect on entrepreneurial decision. The research model was able to explain 62.3% of the variation in entrepreneurial decision. This study confirms that strengthening students' internal factors is more effective in encouraging entrepreneurial decisions. In an incubation ecosystem, internal readiness both cognitive (Sharia financial literacy) and psychological (self-efficacy) proves far more decisive in translating entrepreneurial intent into actual decisions than external social pressure or peer influence.